Semantic Study of Halu' in The Qur'an - N Naifah (Alsina : Journal of Arabic Studies, 2019)
The study aimed to find out the meaning of halu' in the Qur'an, the relationship between halu and Adversity Quotient (AQ), and the Qur’anic management methods to address halu' as well as to enhance the Adversity Quotient (AQ). This study was a descriptive qualitative research with semantic approach. The data were collected through documentation method and analized by means of Syntagmatic Paradigmatic approach. The study found that halu' was a negative human potential to easily complain but hard to share with others because it was triggered by greed. It had potential to cause people to quickly give up, despair, and be selfish, thus causing self-difficulties to face challenges of life. It hampered an individual to be a strong personality and to achieve personal success. Therefore, human needed for specific methods to suppress and manage the negatif potential to avoid its negative effects. Halu' and AQ (Adversity Quotient) had a very close relationship. Halu' could be overcome by improving the level of Adversity Quotient (AQ). Thus, a high Adversity Quotient (AQ) was the solution for the problem of human’s halu'. The Qur’anic management methods in addressing halu' used to improve Adversity Quotient (AQ) were performing prayers, establishing prayers continuously, spending the property for infaq, believing in the day of judgment, feeling fear of the God’s punishment, having sexual intercourse only with a legitimate partner, fulfilling the mandate and promises, enforcing bear testimony, and keeping the prayers quality.